METODE PEMBELAJARAN SHOROF DI PONDOK PESANTRENSUKAHIDENG, SUKARAME, KABUPATEN TASIKMALAYA - Mubarok, Mohammad Husni (Prodi PAI IAILM Suryalaya, 2018)
Reflecting the reality of today, many people have lacked thescience of Shorof, but today is placing more emphasis on public scienceonly, and as if Islamic boarding school were ancient. Even, they assumethat Islamic boarding school certificate can’t be used for apply a job.But, it could lead us to deep dive about theology. This study aims tolearn the shorof learning method of Islamic boarding school along withits sustainability and procrastination factors. This type of research is adescriptive qualitative approach. It’s a research procedure that resultsin both written and oral data from the party which has a directconnection to Shorof learning method. Then, they are fully described indetail and done research. The findings were systematically done. Thelearning contributing factors includes the curriculum in Islamicboarding school, building facilities, and teachers. And, the inhibitionfactors includes the number of students becoming unruly due to a wideIslamic boarding school.